Lightweight high-strength foamed glass and method for producing the same

CN118619557BActive Publication Date: 2026-10-27NORTH CHINA UNIVERSITY OF TECHNOLOGY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410850472.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2026-10-27
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

[0003]随着对建筑行业绿色施工意识的不断提高,我国对建筑业的材料选用更加关注,进而对建筑材料的性能要求更高,但是目前大多数泡沫玻璃在保证孔隙率和轻质的情况下,力学性能会下降较多,从而导致泡沫玻璃在应用方面受到一定的限制

Benefits of technology

[0028]1、本发明采用自制起泡剂,在升温过程中,起泡剂逐渐形成气孔结构,内部包裹气孔,外部与玻璃液连接形成液相体系,冷却后形成稳定的壳体结构,使制得的泡沫玻璃包含大量的玻璃相框架结构,保证轻质的同时力学性能(耐压强度和抗折强度)优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118619557B_ABST
    Figure CN118619557B_ABST
Patent Text Reader

Abstract

The application provides light high-strength foam glass and a preparation method thereof, and belongs to the technical field of foam glass. The light high-strength foam glass is prepared from the following raw materials in parts by weight: 100 parts of a liquefying agent, 20-35 parts of a foaming agent, 0.5-3 parts of a connecting agent and 0.5-10 parts of a charge balancing agent. 3 The preparation method of the foaming agent comprises the following steps: A1, 40 parts of 30wt% dextrin liquid and 5 parts of water glass with a density of 1.4 g / cm 3 are weighed according to parts by weight, and are uniformly mixed to obtain a binding liquid; A2, 35 parts of montmorillonite powder, 35 parts of kaolinite powder, 15 parts of boron glass powder and 15 parts of a foaming substance are weighed according to parts by weight, and are uniformly mixed by using a three-dimensional mixer to obtain a powder mixture; A3, the powder mixture obtained in A2 is transferred into a counter-current stirrer, the binding liquid obtained in A1 is added in the stirring process, and is uniformly mixed, and is introduced into a mold for compression molding, drying at room temperature, crushing and screening through a 20-mesh sieve to obtain the foaming agent. The foam glass prepared by the application has excellent mechanical properties (compressive strength and bending strength) while ensuring light weight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of foam glass technology, specifically relating to a lightweight high-strength foam glass and its preparation method. Background Technology

[0002] Foam glass has the functions of heat insulation, moisture-proofing, fireproofing and corrosion resistance. In addition, glass materials have the advantage of long-term use without deterioration of performance. Therefore, it is widely used in harsh environments such as heat insulation, deep cold, underground, open air, flammable, humid and chemically corrosive environments, as well as in wall insulation, petroleum, chemical industry, computer room noise reduction, highway sound-absorbing isolation walls, power, military products, etc., and is known as a green and environmentally friendly material.

[0003] With the increasing awareness of green construction in the building industry, my country is paying more attention to the selection of building materials and has higher requirements for their performance. However, most foam glass currently suffers from a significant decrease in mechanical properties while maintaining porosity and lightweight, which limits its application.

[0004] Therefore, as a porous material, lightweight and high-strength foam glass has important research significance in the field of engineering materials. Summary of the Invention

[0005] To address the problems existing in the background art, the present invention provides a lightweight high-strength foam glass and its preparation method, which ensures lightweight while maintaining excellent mechanical properties.

[0006] To achieve the above objectives, in a first aspect, the present invention provides the following technical solution:

[0007] A lightweight high-strength foamed glass, by weight, is made of the following raw material components: 100 parts liquefaction agent, 20-35 parts foaming agent, 0.5-3 parts binder and 0.5-10 parts charge balancing agent;

[0008] The foaming agent is prepared as follows:

[0009] A1. Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3 Water glass, mixed well, yields an adhesive solution;

[0010] A2. Weigh 35 parts of montmorillonite powder, 35 parts of kaolinite powder, 15 parts of borosilicate glass powder and 15 parts of foaming agent by weight, and mix them evenly with a three-dimensional mixer to obtain a powder mixture.

[0011] A3. Transfer the powder mixture obtained in A2 into a countercurrent mixer, add the adhesive liquid obtained in A1 during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0012] Through the above technical solution, a mixture of montmorillonite powder, kaolinite powder, and borosilicate glass powder is used to pre-encapsulate the foaming material to obtain a foaming agent. During the heating process, the foaming agent gradually forms a porous structure, with pores encapsulated inside and connected to the molten glass outside to form a liquid phase system. After cooling, a stable shell structure is formed, so that the foamed glass contains a large number of glass phase framework structures, which reduces the density of the product while enhancing the compressive strength and flexural strength of the product, thus obtaining lightweight and high-strength foamed glass.

[0013] Furthermore, the refractory properties of the montmorillonite powder, kaolinite powder, and borosilicate glass powder are all between 450-750℃.

[0014] Furthermore, the particle size of the montmorillonite powder, kaolinite powder, and borosilicate glass powder is all less than 100 mesh.

[0015] Furthermore, the foaming substance includes sodium bicarbonate and / or potassium bicarbonate.

[0016] Furthermore, the particle size of the foaming substance is less than 100 mesh.

[0017] Furthermore, the preparation method of the binder is as follows: by weight, 10 parts of borax are added to 5 parts of water and stirred. Then, 1 part of lanthanum oxide and 1 part of cerium oxide are added and stirred until evenly mixed. The mixture is then dried in an oven at 60-80°C, pulverized, and passed through a 30-mesh sieve to obtain the binder.

[0018] By adopting the above technical solution, borax, lanthanum oxide, and cerium oxide are added to prepare a binder. Borax can lower the softening temperature, and the addition of lanthanum oxide and cerium oxide can improve the density of the thermally conductive layer, making the heating uniform. In synergy with the foaming agent, it ensures uniform and dense pores, thereby achieving an excellent effect of reducing the density of the product.

[0019] Furthermore, the charge balancing agent includes one or a mixture of at least two of vanadium oxide, chromium oxide, manganese oxide, and iron oxide.

[0020] Furthermore, the liquefying agent includes silicon oxide, boron oxide, phosphorus pentoxide, sodium oxide, and aluminum oxide, and the mass ratio of silicon oxide, boron oxide, phosphorus pentoxide, sodium oxide, and aluminum oxide is 35:30:5:20:10.

[0021] Furthermore, the particle size of the liquefying agent is 2-100 μm.

[0022] Secondly, the present invention provides the following technical solution:

[0023] A method for preparing lightweight high-strength foam glass, comprising the following steps:

[0024] S1. By weight, mix 100 parts of liquefying agent, 20-35 parts of foaming agent, 0.5-3 parts of binder and 0.5-10 parts of charge balancing agent to obtain a mixture.

[0025] S2. Inject the mixture obtained in S1 into the mold, heat it to 350-450℃ at a heating rate of 0.5-5℃ / min, and hold it for 30-90min; continue to heat it to 700-800℃ at a heating rate of 0.5-5℃ / min, and hold it for 30-90min; then cool it down to 250-350℃, and hold it for 30-90min; continue to cool it down to room temperature to obtain lightweight high-strength foam glass.

[0026] By adopting the above preparation method, the self-made foaming agent and the binder work synergistically. During the preparation process, the temperature gradient is controlled so that the self-made foaming agent is released and decomposed in a controllable manner, ensuring the number, size and location of pores. By controlling the foaming process and pore structure, porous foam glass with excellent mechanical properties can be obtained.

[0027] This application has the following beneficial effects:

[0028] 1. This invention uses a self-made foaming agent. During the heating process, the foaming agent gradually forms a porous structure, with the pores inside and the external connection with the molten glass to form a liquid phase system. After cooling, a stable shell structure is formed, so that the foamed glass contains a large number of glass phase framework structures, ensuring that it is lightweight while having excellent mechanical properties (compressive strength and flexural strength).

[0029] 2. The borax in the self-made binder of this invention can lower the softening temperature, and the addition of lanthanum oxide and cerium oxide can improve the density of the thermally conductive layer, making it heat-even and ensuring uniform and dense pores, thereby achieving the effect of reducing the density of the product.

[0030] 3. By controlling the temperature gradient, the self-made foaming agent is released and decomposed in a controllable manner, ensuring the number, size and location of pores. By controlling the foaming process and pore structure, porous foam glass with excellent mechanical properties can be obtained. Attached Figure Description

[0031] Figure 1 This is a comparison trend chart of the compressive strength of the foamed glass prepared in Examples 1-5 and Comparative Examples 1-8 of the present invention;

[0032] Figure 2 This is a comparison trend chart of the flexural strength of the foam glass prepared in Examples 1-5 and Comparative Examples 1-8 of the present invention;

[0033] Figure 3 This is a comparison trend chart of the bulk density of the foamed glass prepared in Examples 1-5 and Comparative Examples 1-8 of the present invention. Detailed Implementation

[0034] The present application will be further described in detail below with reference to the embodiments.

[0035] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.

[0036] Example 1

[0037] A method for preparing lightweight high-strength foam glass includes the following steps:

[0038] S1. Ingredients: Mix 100 parts of liquefying agent, 30 parts of foaming agent, 1 part of binder and 2 parts of charge balancing agent by weight to obtain a mixture.

[0039] S2. Molding and flattening: Inject the mixture obtained in S1 into a heat-resistant steel mold and press it flat at a pressure of 0.6 MPa.

[0040] Melting and bubbling: Heat to 400℃ at a heating rate of 1℃ / min and hold for 60min; continue heating to 750℃ at a heating rate of 1℃ / min and hold for 60min.

[0041] Annealing and cooling: Cool to 300℃ and hold for 60 minutes; continue cooling to room temperature to obtain lightweight high-strength foam glass.

[0042] The liquefying agent is a mixture of silicon oxide, boron oxide, phosphorus pentoxide, sodium oxide and aluminum oxide in a mass ratio of 35:30:5:20:10. The particle size of the liquefying agent ranges from 2 to 100 μm, and the particle shape is mainly spherical.

[0043] The preparation method of the foaming agent is as follows:

[0044] A1. Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3 Water glass, mixed well, yields an adhesive solution;

[0045] A2. Weigh 35 parts of montmorillonite powder, 35 parts of kaolinite powder, 15 parts of borosilicate glass powder and 15 parts of foaming agent by weight, and mix them evenly with a three-dimensional mixer to obtain a powder mixture.

[0046] A3. Transfer the powder mixture obtained in A2 into a countercurrent mixer, add the adhesive liquid obtained in A1 during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0047] The refractories of montmorillonite powder, kaolinite powder, and borosilicate glass powder are all between 450-750℃, and the particle size is all less than 100 mesh; the foaming substance is sodium bicarbonate, with a particle size of less than 100 mesh.

[0048] The preparation method of the binder is as follows: by weight, add 10 parts of borax to 5 parts of water, stir, add 1 part of lanthanum oxide and 1 part of cerium oxide, stir and mix evenly, put it in an oven at 60-80℃ to dry, pulverize, and pass through a 30-mesh sieve to obtain the binder.

[0049] The charge balancing agent is vanadium oxide.

[0050] Example 2

[0051] A method for preparing lightweight high-strength foam glass includes the following steps:

[0052] S1. Ingredients: Mix 100 parts of liquefying agent, 20 parts of foaming agent, 0.5 parts of binder and 0.5 parts of charge balancing agent by weight to obtain a mixture.

[0053] S2. Molding and flattening: Inject the mixture obtained in S1 into a heat-resistant steel mold and press it flat at a pressure of 0.6 MPa.

[0054] Melting and bubbling: Heat to 350℃ at a heating rate of 0.5℃ / min and hold for 30 min; continue heating to 700℃ at a heating rate of 0.5℃ / min and hold for 30 min.

[0055] Annealing and cooling: Cool to 250℃ and hold for 30 minutes; continue cooling to room temperature to obtain lightweight high-strength foam glass.

[0056] The liquefying agent is a mixture of silicon oxide, boron oxide, phosphorus pentoxide, sodium oxide and aluminum oxide in a mass ratio of 35:30:5:20:10. The particle size of the liquefying agent ranges from 2 to 100 μm, and the particle shape is mainly spherical.

[0057] The preparation method of the foaming agent is as follows:

[0058] A1. Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3 Water glass, mixed well, yields an adhesive solution;

[0059] A2. Weigh 35 parts of montmorillonite powder, 35 parts of kaolinite powder, 15 parts of borosilicate glass powder and 15 parts of foaming agent by weight, and mix them evenly with a three-dimensional mixer to obtain a powder mixture.

[0060] A3. Transfer the powder mixture obtained in A2 into a countercurrent mixer, add the adhesive liquid obtained in A1 during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0061] The refractories of montmorillonite powder, kaolinite powder, and borosilicate glass powder are all between 450-750℃, and the particle size is all less than 100 mesh; the foaming substance is sodium bicarbonate, with a particle size of less than 100 mesh.

[0062] The preparation method of the binder is as follows: by weight, add 10 parts of borax to 5 parts of water, stir, add 1 part of lanthanum oxide and 1 part of cerium oxide, stir and mix evenly, put it in an oven at 60-80℃ to dry, pulverize, and pass through a 30-mesh sieve to obtain the binder.

[0063] The charge balancing agent is vanadium oxide.

[0064] Example 3

[0065] A method for preparing lightweight high-strength foam glass includes the following steps:

[0066] S1. Ingredients: Mix 100 parts of liquefying agent, 35 parts of foaming agent, 3 parts of binder and 10 parts of charge balancing agent by weight to obtain a mixture.

[0067] S2. Molding and flattening: Inject the mixture obtained in S1 into a heat-resistant steel mold and press it flat at a pressure of 0.6 MPa.

[0068] Melting and bubbling: Heat to 450℃ at a heating rate of 5℃ / min and hold for 90min; continue heating to 800℃ at a heating rate of 5℃ / min and hold for 90min.

[0069] Annealing and cooling: Cool to 350℃ and hold for 90 minutes; continue cooling to room temperature to obtain lightweight high-strength foam glass.

[0070] The liquefying agent is a mixture of silicon oxide, boron oxide, phosphorus pentoxide, sodium oxide and aluminum oxide in a mass ratio of 35:30:5:20:10. The particle size of the liquefying agent ranges from 2 to 100 μm, and the particle shape is mainly spherical.

[0071] The preparation method of the foaming agent is as follows:

[0072] A1. Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3 Water glass, mixed well, yields an adhesive solution;

[0073] A2. Weigh 35 parts of montmorillonite powder, 35 parts of kaolinite powder, 15 parts of borosilicate glass powder and 15 parts of foaming agent by weight, and mix them evenly with a three-dimensional mixer to obtain a powder mixture.

[0074] A3. Transfer the powder mixture obtained in A2 into a countercurrent mixer, add the adhesive liquid obtained in A1 during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0075] The refractories of montmorillonite powder, kaolinite powder, and borosilicate glass powder are all between 450-750℃, and the particle size is all less than 100 mesh; the foaming substance is sodium bicarbonate, with a particle size of less than 100 mesh.

[0076] The preparation method of the binder is as follows: by weight, add 10 parts of borax to 5 parts of water, stir, add 1 part of lanthanum oxide and 1 part of cerium oxide, stir and mix evenly, put it in an oven at 60-80℃ to dry, pulverize, and pass through a 30-mesh sieve to obtain the binder.

[0077] The charge balancing agent is vanadium oxide.

[0078] Example 4

[0079] A method for preparing lightweight high-strength foam glass includes the following steps:

[0080] S1. Ingredients: Mix 100 parts of liquefying agent, 30 parts of foaming agent, 2 parts of binder and 6 parts of charge balancing agent by weight to obtain a mixture.

[0081] S2. Molding and flattening: Inject the mixture obtained in S1 into a heat-resistant steel mold and press it flat at a pressure of 0.6 MPa.

[0082] Melting and bubbling: Heat to 400℃ at a heating rate of 3℃ / min and hold for 60min; continue heating to 750℃ at a heating rate of 3℃ / min and hold for 60min.

[0083] Annealing and cooling: Cool to 300℃ and hold for 60 minutes; continue cooling to room temperature to obtain lightweight high-strength foam glass.

[0084] The liquefying agent is a mixture of silicon oxide, boron oxide, phosphorus pentoxide, sodium oxide and aluminum oxide in a mass ratio of 35:30:5:20:10. The particle size of the liquefying agent ranges from 2 to 100 μm, and the particle shape is mainly spherical.

[0085] The preparation method of the foaming agent is as follows:

[0086] A1. Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3Water glass, mixed well, yields an adhesive solution;

[0087] A2. Weigh 35 parts of montmorillonite powder, 35 parts of kaolinite powder, 15 parts of borosilicate glass powder and 15 parts of foaming agent by weight, and mix them evenly with a three-dimensional mixer to obtain a powder mixture.

[0088] A3. Transfer the powder mixture obtained in A2 into a countercurrent mixer, add the adhesive liquid obtained in A1 during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0089] The refractories of montmorillonite powder, kaolinite powder, and borosilicate glass powder are all between 450-750℃, and the particle size is all less than 100 mesh; the foaming substance is potassium bicarbonate, with a particle size of less than 100 mesh.

[0090] The preparation method of the binder is as follows: by weight, add 10 parts of borax to 5 parts of water, stir, add 1 part of lanthanum oxide and 1 part of cerium oxide, stir and mix evenly, put it in an oven at 60-80℃ to dry, pulverize, and pass through a 30-mesh sieve to obtain the binder.

[0091] The charge balancing agent is chromium oxide.

[0092] Example 5

[0093] A method for preparing lightweight high-strength foam glass includes the following steps:

[0094] S1. Ingredients: Mix 100 parts of liquefying agent, 30 parts of foaming agent, 2 parts of binder and 8 parts of charge balancing agent by weight to obtain a mixture.

[0095] S2. Molding and flattening: Inject the mixture obtained in S1 into a heat-resistant steel mold and press it flat at a pressure of 0.6 MPa.

[0096] Melting and bubbling: Heat to 400℃ at a heating rate of 4℃ / min and hold for 80min; continue heating to 780℃ at a heating rate of 3℃ / min and hold for 70min.

[0097] Annealing and cooling: Cool to 320℃ and hold for 50 minutes; continue cooling to room temperature to obtain lightweight high-strength foam glass.

[0098] The liquefying agent is a mixture of silicon oxide, boron oxide, phosphorus pentoxide, sodium oxide and aluminum oxide in a mass ratio of 35:30:5:20:10. The particle size of the liquefying agent ranges from 2 to 100 μm, and the particle shape is mainly spherical.

[0099] The preparation method of the foaming agent is as follows:

[0100] A1. Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3 Water glass, mixed well, yields an adhesive solution;

[0101] A2. Weigh 35 parts of montmorillonite powder, 35 parts of kaolinite powder, 15 parts of borosilicate glass powder and 15 parts of foaming agent by weight, and mix them evenly with a three-dimensional mixer to obtain a powder mixture.

[0102] A3. Transfer the powder mixture obtained in A2 into a countercurrent mixer, add the adhesive liquid obtained in A1 during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0103] The refractories of montmorillonite powder, kaolinite powder, and borosilicate glass powder are all between 450-750℃, and the particle size is all less than 100 mesh; the foaming substance is a mixture of sodium bicarbonate and potassium bicarbonate, with a mass ratio of sodium bicarbonate to potassium bicarbonate of 1:1, and the particle size is less than 100 mesh.

[0104] The preparation method of the binder is as follows: by weight, add 10 parts of borax to 5 parts of water, stir, add 1 part of lanthanum oxide and 1 part of cerium oxide, stir and mix evenly, put it in an oven at 60-80℃ to dry, pulverize, and pass through a 30-mesh sieve to obtain the binder.

[0105] The charge balancing agent is a mixture of vanadium oxide and chromium oxide in a mass ratio of 1:1.

[0106] Comparative Example 1

[0107] The only difference between this comparative example and Example 1 is that the foaming agent used is sodium bicarbonate, a foaming substance.

[0108] Comparative Example 2

[0109] The only difference between this comparative example and Example 1 is that montmorillonite powder, kaolinite powder, and borosilicate glass powder are removed from the preparation of the foaming agent.

[0110] Specifically, the foaming agent is prepared as follows:

[0111] Weigh 40 parts by weight of dextrin solution (30wt%) and 5 parts by weight of water glass (density 1.4g / cm3), mix them evenly to obtain the adhesive solution.

[0112] Weigh 100 parts of sodium bicarbonate and transfer it into a countercurrent mixer. Add the adhesive liquid during the mixing process, mix evenly, press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0113] Comparative Example 3

[0114] The only difference between this comparative example and Example 1 is that montmorillonite powder is removed in the preparation of the foaming agent.

[0115] Specifically, the preparation method of the foaming agent is as follows:

[0116] A1. Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3 Water glass, mixed well, yields an adhesive solution;

[0117] A2. Weigh 70 parts by weight of kaolinite powder, 15 parts by weight of borosilicate glass powder and 15 parts by weight of foaming substance, and mix them evenly with a three-dimensional mixer to obtain a powder mixture.

[0118] A3. Transfer the powder mixture obtained in A2 into a countercurrent mixer, add the adhesive liquid obtained in A1 during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0119] Comparative Example 4

[0120] The only difference between this comparative example and Example 1 is that kaolinite powder is removed from the preparation of the foaming agent.

[0121] Specifically, the preparation method of the foaming agent is as follows:

[0122] A1. Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3 Water glass, mixed well, yields an adhesive solution;

[0123] A2. Weigh 70 parts of montmorillonite powder, 15 parts of borosilicate glass powder and 15 parts of foaming agent by weight, and mix them evenly with a three-dimensional mixer to obtain a powder mixture.

[0124] A3. Transfer the powder mixture obtained in A2 into a countercurrent mixer, add the adhesive liquid obtained in A1 during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0125] Comparative Example 5

[0126] The only difference between this comparative example and Example 1 is that borosilicate glass powder is removed in the preparation of the foaming agent.

[0127] Specifically, the preparation method of the foaming agent is as follows:

[0128] A1. Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3 Water glass, mixed well, yields an adhesive solution;

[0129] A2. Weigh 50 parts of montmorillonite powder, 35 parts of kaolinite powder and 15 parts of foaming agent by weight, and mix them evenly with a three-dimensional mixer to obtain a powder mixture.

[0130] A3. Transfer the powder mixture obtained in A2 into a countercurrent mixer, add the adhesive liquid obtained in A1 during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0131] Comparative Example 6

[0132] The only difference between this comparative example and Example 1 is that the foaming agent is not prepared using a three-dimensional mixer, but is mixed directly in a countercurrent mixer.

[0133] Specifically, the preparation method of the foaming agent is as follows:

[0134] Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3 Water glass, mixed well, yields an adhesive solution;

[0135] Weigh out 35 parts by weight of montmorillonite powder, 35 parts by weight of kaolinite powder, 15 parts by weight of borosilicate glass powder and 15 parts by weight of foaming agent, transfer them into a countercurrent mixer, add the adhesive liquid during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent.

[0136] Comparative Example 7

[0137] The only difference between this comparative example and Example 1 is that lanthanum oxide and cerium oxide are removed in the preparation of the binder.

[0138] Specifically, the preparation method of the binder is as follows: by weight, add 10 parts of borax to 5 parts of water, stir, mix evenly, dry in an oven at 60-80℃, pulverize, and pass through a 30-mesh sieve to obtain the binder.

[0139] Comparative Example 8

[0140] The only difference between this comparative example and Example 1 is that the foaming agent is directly sodium bicarbonate, and lanthanum oxide and cerium oxide are removed in the preparation of the binder.

[0141] Specifically, the foaming agent is sodium bicarbonate, a foaming substance; and the preparation method of the binder is as follows: by weight, 10 parts of borax are added to 5 parts of water, stirred, mixed evenly, dried in an oven at 60-80℃, pulverized, and passed through a 30-mesh sieve to obtain the binder.

[0142] Experimental Example 1

[0143] The compressive and flexural strengths of the foam glass prepared in Examples 1-5 and Comparative Examples 1-8 were tested using an electronic universal testing machine (Shenzhen Xin Sansi Materials Testing Co., Ltd.) according to GB / T 5486-2008. The test results are shown in Table 1 and 2. Figure 1-2 .

[0144] Experimental Example 2

[0145] According to JC / T 647-2014, the densities of the foamed glass prepared in Examples 1-5 and Comparative Examples 1-8 were tested, and the test results are shown in Table 1 and 2. Figure 3 .

[0146] Table 1. Performance test data of foamed glass obtained in Examples 1-5 and Comparative Examples 1-8

[0147] Example 1 2.5 2.2 0.21 Example 2 2.6 2.2 0.21 Example 3 2.5 2.3 0.20 Example 4 2.4 2.3 0.20 Example 5 2.5 2.2 0.21 Comparative Example 1 1.4 1.3 0.32 Comparative Example 2 1.5 1.3 0.31 Comparative Example 3 2.2 2.0 0.23 Comparative Example 4 2.3 1.9 0.22 Comparative Example 5 2.3 2.0 0.22 Comparative Example 6 2.1 1.8 0.25 Comparative Example 7 2.2 1.9 0.21 Comparative Example 8 0.9 0.8 0.33

[0148] Results Analysis: Analyze Examples 1-5 and combine the data in Table 1 and... Figure 1-3 As can be seen, the foam glass produced by this invention ensures lightweight (density 0.20 g / cm³). -3 At the same time, it has excellent mechanical properties, with a compressive strength of over 2.4 MPa and a flexural strength of over 2.2 MPa.

[0149] Analysis of Example 1 and Comparative Examples 1-8, combined with data from Table 1 and Figure 1-2 It can be seen that the use of homemade foaming agents can significantly enhance the compressive and flexural strength of the final foamed glass. In the preparation of homemade foaming agents, montmorillonite powder, kaolinite powder, and borosilicate glass powder are indispensable; the absence of any one of them will lead to a decrease in compressive and flexural strength. In the preparation of homemade binders, the addition of lanthanum oxide and cerium oxide to borax also enhances the compressive and flexural strength of the final foamed glass. Furthermore, homemade foaming agents and homemade binders can produce a synergistic effect in enhancing the compressive and flexural strength of foamed glass.

[0150] Analysis of Example 1 and Comparative Examples 1-8, combined with data from Table 1 and Figure 3 It can be seen that the use of homemade foaming agents can significantly reduce the density of the final foam glass, making the foam glass lighter.

[0151] The inventors speculate that the principle behind the aforementioned effect is as follows: A mixture of montmorillonite powder, kaolinite powder, and borosilicate glass powder is used to pre-coat the foaming substance, creating powdery granules. At low temperatures, the foaming substance decomposes, generating a large amount of gas, forming a cavity structure within the granular foaming agent. With continued heating, the surface of the foaming agent gradually softens into a viscous liquid, which expands under the influence of the internal gas. At this point, the viscosity of the liquefied agent also changes, gradually forming molten glass. Due to the good compatibility between the viscous liquid on the foaming agent surface and the molten glass, a complete liquid-phase system is formed. After cooling, the two connect to form a stable framework system. The increased porosity enhances both compressive and flexural strength, resulting in a high-strength porous product.

[0152] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0153] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A lightweight, high-strength foam glass, characterized in that, It is made from the following raw material components by weight: 100 parts liquefaction agent, 20-35 parts foaming agent, 0.5-3 parts binder and 0.5-10 parts charge balancing agent; The foaming agent is prepared as follows: A1. Weigh out 40 parts by weight of 30wt% dextrin solution and 5 parts by weight of solution with a density of 1.4 g / cm³. 3 Water glass, mixed well, yields an adhesive solution; A2. Weigh 35 parts of montmorillonite powder, 35 parts of kaolinite powder, 15 parts of borosilicate glass powder and 15 parts of foaming agent by weight, and mix them evenly with a three-dimensional mixer to obtain a powder mixture. A3. Transfer the powder mixture obtained in A2 into a countercurrent mixer, add the adhesive liquid obtained in A1 during the mixing process, mix well, pour into a mold and press into shape, dry at room temperature, pulverize, and pass through a 20-mesh sieve to obtain the foaming agent. The refractory properties of the montmorillonite powder, kaolinite powder, and borosilicate glass powder are all between 450-750℃; the foaming substance includes sodium bicarbonate and / or potassium bicarbonate; the preparation method of the binder is as follows: by weight, 10 parts of borax are added to 5 parts of water, stirred, 1 part of lanthanum oxide and 1 part of cerium oxide are added, stirred and mixed evenly, dried in an oven at 60-80℃, pulverized, and passed through a 30-mesh sieve to obtain the binder; the charge balancing agent includes one or a mixture of at least two of vanadium oxide, chromium oxide, manganese oxide, and iron oxide; the liquefying agent includes silicon oxide, boron oxide, phosphorus pentoxide, sodium oxide, and aluminum oxide, and the mass ratio of silicon oxide, boron oxide, phosphorus pentoxide, sodium oxide, and aluminum oxide is 35:30:5:20:

10.

2. The lightweight high-strength foam glass according to claim 1, characterized in that, The particle size of the montmorillonite powder, kaolinite powder, and borosilicate glass powder is all less than 100 mesh.

3. The lightweight high-strength foam glass according to claim 1, characterized in that, The particle size of the foaming substance is less than 100 mesh.

4. The lightweight high-strength foam glass according to claim 1, characterized in that, The particle size of the liquefying agent is 2-100 μm.

5. A method for preparing lightweight high-strength foamed glass, characterized in that, The method for preparing the lightweight high-strength foam glass as described in any one of claims 1-4 comprises the following steps: S1. By weight, mix 100 parts of liquefying agent, 20-35 parts of foaming agent, 0.5-3 parts of binder and 0.5-10 parts of charge balancing agent to obtain a mixture. S2. Inject the mixture obtained in S1 into the mold, heat it to 350-450℃ at a heating rate of 0.5-5℃ / min, and hold it for 30-90min; continue to heat it to 700-800℃ at a heating rate of 0.5-5℃ / min, and hold it for 30-90min; then cool it down to 250-350℃, and hold it for 30-90min; continue to cool it down to room temperature to obtain lightweight high-strength foam glass.

Citation Information

Patent Citations

  • Foamed glass particles and preparation method thereof

    CN112266173A

  • Mixture for producing foamed glass

    RU2540719C1